EVALUASI KEPUASAN PASIEN RAWAT JALAN TERHADAP KUALITAS PELAYANAN KEFARMASIAN DI PUSKESMAS BANDAR JAYA KECAMATAN TERBANGGI BESAR LAMPUNG TENGAH - , YUDHA ABDILLAH, Anna Wahyuni Widayanti, MPH, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted as seeing a high number of visits and the number of prescriptions entered in Bandar Jaya Community Health Center, District of Terbanggi Besar, Central Lampung. This study aimed to examine the effect of level of Quality of Pharmaceutical Services at Community Health Center Pharmacy in Bandar Jaya, District of Terbanggi Besar, Central Lampung on patient satisfaction views of the five SERVQUAL dimensions (reliability, responsiveness, assurance, empathy, tangible). This study is non-experimental observations performed on outpatients who received services at pharmacy in Community Health Centers of Bandar Jaya. The sample used in this study is 110 respondents. The sampling method using purposive sampling. Methods of data analysis performed using a questionnaire that was tested first for validity and reliability. The analysis conducted in this study is testing the characteristics of respondents, services and expectations test, mean gap test, and analysis of the Cartesian diagram. The results of the analysis of the mean gap, the highest negative mean gap value is the reliability dimension (-0.47), followed by tangible dimension as well as responsiveness and assurance dimension (-0.26) and dimension of empathy (-0.23). From the analysis of the mean gap in expectations and services overall mean gap value obtained is -0.28. So it can be concluded that the majority of patients are still not satisfied with the services provided by the Pharmacy in Bandar Jaya Community Health Center, District of Terbanggi Besar, Central Lampung. The results of the analysis of Cartesian diagram showed that the dimension of reliability occupies of quadrant B which dimensions lies in that quadrant is necessary to reform the quality of service.